Susceptibility to the ‘Dark Side’ of Goal-Setting: Does Moral Justification Influence the Effect of Goals on Unethical Behavior? - Niven, Karen (Journal of business ethics, 2016)
Setting goals in the workplace can motivate improved performance but it might also compromise ethical behavior. In this paper, we propose that individual differences in the dispositional tendency to morally justify behavior moderate the effects of specific performance goals on unethical behavior. We conducted an experimental study in which working participants, who were randomly assigned to a specific goal condition or to a condition with a vague goal that lacked a specific target (i.e., ‘do your best’), completed two tasks in which they had the opportunity to act unethically. In an ethical dilemma task, participants in the specific goal condition were more likely to advocate using unethical methods. However, in an anagram task, only those with high moral justification overstated their performance to a greater degree in the specific goal condition. As such, individuals may not be equally susceptible to the ‘dark side’ of goal-setting.